2016
DOI: 10.4269/ajtmh.16-0177
|View full text |Cite
|
Sign up to set email alerts
|

Defining Population Health Vulnerability Following an Extreme Weather Event in an Urban Pacific Island Environment: Honiara, Solomon Islands

Abstract: Abstract. Extreme weather events are common and increasing in intensity in the southwestern Pacific region. Health impacts from cyclones and tropical storms cause acute injuries and infectious disease outbreaks. Defining population vulnerability to extreme weather events by examining a recent flood in Honiara, Solomon Islands, can help stakeholders and policymakers adapt development to reduce future threats. The acute and subacute health impacts following the April 2014 floods were defined using data obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…(1) Yes (2) Unable to test (1a) These associations were strongest for bacterial and all-cause diarrhea (1b) The strongest positive associations were 4-7 days after flood events (2) Studies often did not report the length of flood events in the literature 26 articles (Abu and Codjoe 2018, Cash et al 2014, Cesa et al 2016, Colston et al 2020, Deilami et al 2017, Fredrick et al 2015Gao et al 2016, Gertler et al 2015, Gong et al 2019, Jones et al 2016, Koley et al 2014, Liu X et al 2016, Liu Z et al 2018, Martinez et al 2016, Natuzzi et al 2016, Rosinger 2018, Saulnier et al 2018, Song Q et al 2018, Thompson et al 2015…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
“…(1) Yes (2) Unable to test (1a) These associations were strongest for bacterial and all-cause diarrhea (1b) The strongest positive associations were 4-7 days after flood events (2) Studies often did not report the length of flood events in the literature 26 articles (Abu and Codjoe 2018, Cash et al 2014, Cesa et al 2016, Colston et al 2020, Deilami et al 2017, Fredrick et al 2015Gao et al 2016, Gertler et al 2015, Gong et al 2019, Jones et al 2016, Koley et al 2014, Liu X et al 2016, Liu Z et al 2018, Martinez et al 2016, Natuzzi et al 2016, Rosinger 2018, Saulnier et al 2018, Song Q et al 2018, Thompson et al 2015…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
“…All questionnaires had informed consent. Not all studies acknowledged the ethical considerations of their work (Natuzzi et al, 2016;Zakrison, Valdes, & Shultz, 2020).…”
Section: Overviewmentioning
confidence: 99%
“…Building and physical infrastructures, such as energy and water systems, were reported to be unreliable or perceived to be inadequate to safely protect staff and patients while providing healthcare services (Natuzzi et al, 2016;Zhong et al, 2014). Specifically, one island nation reported that three of nine health clinics were recently damaged by floodwaters with subsequent geographical information system (GIS) results predicting vulnerability of 75 percent of health systems in future flood events (Natuzzi et al, 2016). Hospital safety concerns, including backup power and water in 61 percent of hospitals surveyed in China, prompted preemptive hospital evacuation as part of their disaster plan (Zhong et al, 2014).…”
Section: Key Themesmentioning
confidence: 99%
“… 27 In this issue of the American Journal of Tropical Medicine and Hygiene , Natuzzi and others detail the human costs associated with this phenomenon. 28 …”
Section: Assessing Health Vulnerabilities In the Solomon Islandsmentioning
confidence: 99%